Chicken, pig, cow on the move - Ohi, Ruth (Toronto ; New York : Annick Press, 2009)
The animals grow restless and search for a perfect new place to live.
On cover: A Ruth Ohi picture book.
Keywords: Chickens; Swine; Cows; Poulets; Porcs; Vaches